Multi-decadal climatology of Polar Lows over the North Pacific by regional climate model - Chen, Fei (Staats- und Universitätsbibliothek Hamburg Carl von Ossietzky, 2013)
The North Pacific is an area where frequently sub-synoptic Polar Lows form in the cold season, especially over the Japan Sea, Bering Sea and Gulf of Alaska. So far, a multi-decadal climatology of such Polar Lows based on individual cases has not been assembled. Here, we consider for this task a dynamical downscaling method for constructing realistically the formation and life cycles during the past decades without exploiting sub-synoptic information in initial fields. A regional climate model is conditioned by large-scale information of NCEP re-analyses. Firstly, we tested the approach by examining its skill in simulating ten known cases of North Pacific Polar Lows. Three of these are discussed in some detail. The signatures of all storms emerge in the simulations with additional sub-synoptic details. The tracks of the simulated Polar Lows follow closely the tracks derived from satellite imagery. We conclude that the suggested method is suitable for constructing multi-decade climatologies, including trends and variability, of Polar Lows in the North Pacific by dynamically downscaling NCEP re-analyses. Secondly, the 6-hourly 1948-2010 NCEP 1 re-analyses have been dynamically downscaled for the region of the North Pacific. With a detecting-and-tracking algorithm a climatology of North Pacific Polar Lows has been constructed. This derived climatology is consistent with the limited observational evidence in terms of frequency and spatial distribution. The climatology exhibits strong year-to-year variability but weak decadal variability and a small positive trend. A Canonical Correlation Analysis describes the conditioning of the formation of Polar Lows by characteristic seasonal mean flow regimes, which favor, or limit, cold air outbreaks and upper air troughs. Associated Correlation Pattern is introduced to describe the relationship between time series of Polar Low occurrence and the geo-potential height from sea level to the upper troposphere and the lower stratosphere. The results indicate that the relationship ...